2021
DOI: 10.1111/1759-7714.13945
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of galectin‐3 expression in patients with resected NSCLC treated with platinum‐based adjuvant chemotherapy

Abstract: Background Galectin‐3 (GAL3), a protein encoded by the LGALS3 gene, plays diverse roles in cancer initiation, progression, and drug resistance. Accordingly, high GAL3 expression in tumor cells is associated with poor prognosis in non‐small cell lung cancer (NSCLC). However, the prognostic impact of GAL3 expression on patients with resected NSCLC receiving platinum‐based adjuvant chemotherapy (AC) remains unclear. This study aimed to determine the prognostic significance of GAL3 expression in NSCLC patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…In consequence, our results revealed that the secretion of sGAL‐3 on resected LUAD patients' plasma (in a validation set) is an independent prognostic biomarker for RFS and OS. In accordance with our results, previous studies in early NSCLC reported that GAL‐3 expression on tumor cells has been reported to be associated with progression, poor prognosis and recurrence after radical resection on tissue samples [ 61 ]. Using non‐invasive methodologies, Yoko Kataoka et al.…”
Section: Discussionsupporting
confidence: 93%
“…In consequence, our results revealed that the secretion of sGAL‐3 on resected LUAD patients' plasma (in a validation set) is an independent prognostic biomarker for RFS and OS. In accordance with our results, previous studies in early NSCLC reported that GAL‐3 expression on tumor cells has been reported to be associated with progression, poor prognosis and recurrence after radical resection on tissue samples [ 61 ]. Using non‐invasive methodologies, Yoko Kataoka et al.…”
Section: Discussionsupporting
confidence: 93%
“… 46 This method was used to evaluate the semi-quantitative expression of target proteins using the following formula: immunoreactivity score = staining intensity score (0: no staining, 1: weak, 2: moderate, and 3: strong staining) × proportion of positive cells score. 47 The expression level of target proteins was considered “low expression” if the H-score was 0–4 and “high expression” if the score was 5–9.…”
Section: Methodsmentioning
confidence: 99%
“…Gal-3 overexpression has been associated with poor prognosis and lower patient survival rates in different types of cancer [ 150 , 173 178 ].…”
Section: Introductionmentioning
confidence: 99%